Case Report: Expanding the phenotypic spectrum of PURA syndrome in South America with the first presentation of concurrent vitiligo - Mora-Martinez, S.; Castaño-Giraldo, Natalia; Nati-Castillo, Humberto Alejandro; Barahona Machado, Laura; Mora Arbeláez, Tatiana; Gordillo-Gonzalez, G.; Izquierdo-Condoy, Juan S. (Frontiers in Pediatrics, 2024)
Purine-rich element-binding protein A (PURα) regulates multiple cellular processes. Rare de novo mutations can lead to PURA syndrome, which manifests as a range of multisystem disturbances, including hypotonia, global developmental delay, swallowing disorders, apnea, seizures, visual impairments, and congenital heart defects. We report the case of a Colombian girl with no relevant medical history who was diagnosed with PURA syndrome at the age of 7, due to a heterozygous mutation located at 5q31.2, specifically the variant c.697_699del (p.Phe233del), in exon 1 of the PURA gene. This represents the first documented case of PURA syndrome in South America and the first association of the syndrome with vitiligo, thereby expanding the known phenotypic spectrum. In addition to enriching the literature concerning the phenotypic diversity of PURA syndrome, this report highlights, for the first time, the diagnostic challenges faced by developing countries like Colombia in diagnosing high-burden rare diseases such as PURA syndrome.